P417 High interest in syphilis pre- and post-exposure prophylaxis among gay, bisexual and other MSM in vancouver and toronto. (14th July 2019) - Fusca, Laura; Hull, Mark; Ross, Patrick; Grennan, Troy; Burchell, Ann; Bayoumi, Ahmed; Tan, Darrell
Abstract : Background: Novel strategies for preventing bacterial sexually transmitted infections (STIs) are urgently needed. We assessed the acceptability of doxycycline-based syphilis pre- and post- exposure prophylaxis (PrEP/PEP) in a survey of gay, bisexual and other men who have sex with men (gbMSM) at risk. Methods: We recruited gbMSM from Toronto and Vancouver sexual health clinics during routine visits from 06/2018-08/2018. The questionnaire included demographics, sexual history/behaviours and knowledge/opinions regarding STI prevention. We analyzed data using descriptive statistics and constructed separate multivariable logistic regression models for willingness to use syphilis PrEP and PEP, with number of male partners in the last six months as the primary predictor, controlling for city, self-perceived syphilis risk, prior syphilis, concern about STI acquisition, number of different STIs previously diagnosed, depression, problem drug use and previous/existing HIV PrEP/PEP use. Results: Among 424 participants, 56.4%/43.6% were recruited in Toronto/Vancouver. Median (interquartile range) age was 31.0 (26.0, 39.0) years, 61.7% had completed postsecondary education and 54.4% were White. Median number of male partners in the past 6 months was 6.0 (3.0, 13.0), and 18.2% had ≥1 prior syphilis diagnosis. 60.1% and 44.1% indicated willingness to use syphilis PEP and PrEP respectively; 36.6% were unwilling to use either. Most participants were familiar with antibiotic resistance (89.0%) and agreed that syphilis rates are rising in Canada (68.2%), but only 55.4% believed they were at risk for syphilis. Agreement with the latter statement was significantly associated with willingness to use syphilis PrEP (aOR=1.6; 95%CI=1.0, 2.5), as was previous/existing HIV PrEP use (aOR=2.2;95%CI=1.1, 4.3) and being "very concerned" about STI acquisition (aOR=1.9;95%CI=1.0, 3.4). Odds of being willing to use syphilis PEP were higher in Toronto versus Vancouver (aOR=2.0;95%CI=1.2, 3.4) and increased with the number of different STIs previously diagnosed (aOR=1.4;95%CI=1.2, 1.7). Conclusion: There is considerable interest in syphilis PrEP/PEP in gbMSM attending STI clinics in Toronto and Vancouver. Further research on such approaches is warranted. Disclosure: No significant relationships.